Abundance of zooplankton during POLARSTERN cruise ARK-IV/3 (PS11) - Mumm, Nicolai; Hirche, Hans-Juergen (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2026)
Abundances of zooplankton taxa were calculated in the Arctic Ocean during Polarstern cruise ARK-IV/3. Samples were taken with the Multinet midi (Hydrobios, Kiel), which is equipped with nine nets (mesh size: 150 µm).
Keywords: Arctic Ocean; Calanus; Copepoda; Zooplankton